An investigation of issues of privacy, anonymity and multi-factor authentication in an open environment - Miles, Shaun Graeme (Rhodes University, Faculty of Science, Department of Computer Science)
This thesis performs an investigation into issues concerning the broad area ofIdentity and Access Management, with a focus on open environments. Through literature research the issues of privacy, anonymity and access control are identified. The issue of privacy is an inherent problem due to the nature of the digital network environment. Information can be duplicated and modified regardless of the wishes and intentions ofthe owner of that information unless proper measures are taken to secure the environment. Once information is published or divulged on the network, there is very little way of controlling the subsequent usage of that information. To address this issue a model for privacy is presented that follows the user centric paradigm of meta-identity. The lack of anonymity, where security measures can be thwarted through the observation of the environment, is a concern for users and systems. By an attacker observing the communication channel and monitoring the interactions between users and systems over a long enough period of time, it is possible to infer knowledge about the users and systems. This knowledge is used to build an identity profile of potential victims to be used in subsequent attacks. To address the problem, mechanisms for providing an acceptable level of anonymity while maintaining adequate accountability (from a legal standpoint) are explored. In terms of access control, the inherent weakness of single factor authentication mechanisms is discussed. The typical mechanism is the user-name and password pair, which provides a single point of failure. By increasing the factors used in authentication, the amount of work required to compromise the system increases non-linearly. Within an open network, several aspects hinder wide scale adoption and use of multi-factor authentication schemes, such as token management and the impact on usability. The framework is developed from a Utopian point of view, with the aim of being applicable to many situations as opposed to a single specific domain. The framework incorporates multi-factor authentication over multiple paths using mobile phones and GSM networks, and explores the usefulness of such an approach. The models are in tum analysed, providing a discussion into the assumptions made and the problems faced by each model.,Adobe Acrobat Pro 9.5.1,Adobe Acrobat 9.51 Paper Capture Plug-in
Keywords: Electronic data processing departments -- Security measures; Electronic data processing departments; Privacy, Right of; Computer security; Data protection; Computers -- Access control